2016
DOI: 10.3233/bmr-150595
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preoperative non-invasive cardiac tests on delay to surgery and subsequent mortality in elderly patients with hip fracture

Abstract: Unnecessary cardiac tests in elderly patients with hip fracture led to a delay in their surgery, yet did not change their cardiac treatment plan. This delay in obtaining hip fracture surgery increases complication rates, hospitalization duration, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Nevertheless, delaying surgery with a cardiac consultation that is not recommended or contributing could lead to worse outcome. Cardiac consultations increase delay to surgery, which is confirmed by several other studies [7,20]. However, in this study, no significant differences in postoperative complications in the overscreening group vs correctly screened patients were found, which may be due to a small sample size.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, delaying surgery with a cardiac consultation that is not recommended or contributing could lead to worse outcome. Cardiac consultations increase delay to surgery, which is confirmed by several other studies [7,20]. However, in this study, no significant differences in postoperative complications in the overscreening group vs correctly screened patients were found, which may be due to a small sample size.…”
Section: Discussionsupporting
confidence: 84%
“…reviewed the effect of preoperative non-invasive cardiac test on hip fracture patients and found that further cardiac test led to a significant delay to surgery [16]. Cluett et al compared the outcomes between the patients with cardiac evaluation besides electrocardiograph (22 patients) and the control group with only electrocardiograph (86 patients), which found the patients with further cardiac test had obvious surgery delay [17].…”
Section: Discussionmentioning
confidence: 99%
“…Ricci et al [23] demonstrated that preoperative cardiac testing (DTS, echocardiography, and cardiac catheterization) did not change the management of perioperative orthopedic surgery or medical therapy in elderly patients with hip fractures but did incur a huge cost of over $47 million annually in the USA; patients undergoing cardiac testing had a delay to surgery on average 3.3 days, which was 1.4 days greater than those who did not. Multiple studies have also demonstrated that preoperative cardiac testing with echocardiography delays surgery without a significant change in preoperative cardiac medications or anesthesia [14,[24][25][26]. In addition, the cost of a thallium test is 261.22 dollars at our institution.…”
Section: Discussionmentioning
confidence: 99%